Fine Flounder (Paralichthys adspersus) Microbiome Showed Important Differences between Wild and Reared Specimens - Ramírez, Carolina; Romero, Jaime (Frontiers in Microbiology, 2017)
The intestinal microbiota is involved in a wide range of biological processes that benefit the host, including providing nutrition and modulating the immune system. Fine flounder (Paralichthys adspersus) is a flatfish of commercial interest that is native to the Chilean coast. The high value of this flatfish has prompted the development of stock enhancement and aquaculture activities. Knowledge of microbiota may help to improve the cultivation of this species; however, few comparative studies have evaluated the intestinal microbiota composition in farmed versus wild fishes. Intestinal contents from wild and aquaculture fish were collected, and DNA was extracted. Subsequently, the V3-region of 16S rRNA was PCR amplified and sequenced using the Ion Torrent platform. The comparison between wild and aquaculture specimens revealed important differences in the composition of the microbiota. The most abundant phylum in wild flounder was Proteobacteria, with an average relative abundance of 68.1 ± 15.4%; in contrast, in aquaculture flounder, this phylum had an average relative abundance of 30.8% ± 24.1%. Reciprocally, the most abundant phylum in flounder aquaculture was Firmicutes, averaging 61.2 ± 28.4%; in contrast, this phylum showed low abundance in wild flounder, in which it averaged 4.7% ± 4%. The phylum Actinobacteria showed greater abundance in wild flounder, ranging from 21.7 ± 18.8%, whereas it averaged only 2.7% ± 3.8% in aquaculture fish. Specific taxa that were differentially distributed between wild and aquaculture flounder were identified using a statistical approach. At the genus level, a total of four genera were differentially represented between the two conditions. Bacillus and Pseudomonas were more highly represented in aquaculture flounder, whereas Arthrobacter and Psychrobacter were observed in wild flounder. Furthermore, in both cases, predicted functions (metabolic pathways) indicated that those microbiota might provide beneficial effects for the host, but wild flounder showed more noteworthy pathways (EPA/DHA, SCFA, biotin). Our results highlight the differences in the microbiota composition between wild and reared fish. Knowing the composition of the intestinal microbiota of P. adspersus is the first step toward exploring the proper management of this species, as well as toward the development of probiotics and functional foods based on their requirements.